“O corpo define ela como mulher”! : uma análise discursiva de entrevistas com homens cis heterossexuais e travestis e mulheres transexuais - Denardin, Jaqueline Angelo dos Santos (2023)
This thesis addresses as a theme: discussions related to discourses about and for the body of travesti 2subjects and transsexual women and the desire of heterosexual cisgender men for these women and/or their bodies. Our objective: is to problematize how the body defines a subject as a woman, as well as how and why the body of these t travesti and transsexual women is the object of desire of heterosexual cisgender men. It is not the intention of this work to exclude any type of manifestation of sexualities and genders, however, in this work our analytical approach will lend itself to interpreting only discursive sequences of heterosexual cisgender men and travesti and transsexual women who are participants in this research. This research has a qualitative character, the methodology: to collect the data and form the corpus that will be analyzed in this research, it was produced through an interview with seventeen participants, being interviewed one participant at a time, who are identified by codenames in order to protect their identity as legally foreseen in ethical issues, these interviews were transcribed in a way that resulted in five hundred and thirty discursive sequences. Not all discursive sequences will be analyzed, as we selected those that present discursive regularities under the body as an 'archetype' for being a woman, as well as the discursive regularities that evidence this body as an object of desire for these heterosexual cisgender men, which are our two analysis categories. Our theoretical framework for this movement of interpretation and dialogue with discursive sequences is based on authors of Discourse Analysis of the French line and following a perspective of applied linguistics of being transgressive and interdisciplinary, it also makes use of concepts from other disciplines such as sociology, history, psychoanalysis, among others. Therefore, what this work shows us as possible conclusions so far is that the discourses (re)produced by both travesti and transsexual women, as well as by heterosexual cisgender men, is that the body alone does not define a subject as a woman, but social and discursive practices, as well as the desire of heterosexual cisgender men is not related to the body as a whole, but to the possibility of exercising their compulsory heterosexuality by relating to a travesti or transsexual woman. Therefore, we still hope with this work to provoke discussions about this theme, because what constitutes us is incompleteness.